Turn-Taking Mechanism in Piers Morgan Uncensored Talkshow: Going Down For LIFE Piers Morgan Discusses the Downfall of Diddy - Rahmah, Nazma Sania; Ruminda, Ruminda; Assiddiqi, Hasbi (Riwayat: Educational Journal of History and Humanities, 2025)
This research analyzes how the turn of conversation on Piers Morgan Uncensored Talkshow episode Going Down Forlife Piers Morgan Discusses The Downfall of Diddy, using Jacob L Mey, (2001) conversation analysis theory as a framework. This research analyzes taking the floor, holding the floor, and yielding the floor through a qualitative examination of the conversation that took place between Piers Morgan and his guest. This study analyzes how the turn of conversation on the piers morgan talk-show in the episode going down for life thr downfall of diddy, using Jacob L. Mey's theory of conversation analysis as a framework. This research identifying the type of turn-taking mechanism used in the conversation. The method used in this research is descriptive qualitative method to produce precise and factual conclusions by using approaches to collect data. The result shows that holding the floor most common used in the conversation that happened in this talk show.